2003
DOI: 10.1148/radiol.2263011737
|View full text |Cite
|
Sign up to set email alerts
|

Coarse Nodular US Pattern in Hepatic Cirrhosis: Risk for Hepatocellular Carcinoma

Abstract: The coarse nodular pattern is more often seen in patients with HDV-related cirrhosis, and, in this setting (in contrast to HBV-, HCV-, and ALC-related cirrhosis, as well as in PBC), it does not represent an added risk factor for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 29 publications
(30 reference statements)
1
39
0
Order By: Relevance
“…Studies in the literature have demonstrated that steatosis is associated with a rapid progression of the hepatic fibrosis and a poor response to the antiviral therapy in hepatitis C patients (27,28) . A precise measurement of the hepatic parenchyma attenuation coefficients is essential for determining a patient's eligibility for a living-donor transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have demonstrated that steatosis is associated with a rapid progression of the hepatic fibrosis and a poor response to the antiviral therapy in hepatitis C patients (27,28) . A precise measurement of the hepatic parenchyma attenuation coefficients is essential for determining a patient's eligibility for a living-donor transplant.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce interobserver variability of both operators, a set of standard images with H, BL, C, and CSNP was used to assess echo patterns as in Caturelli's work and Kitamura's work figures for the CLNP [11,14].…”
Section: Abdominal Ultrasound Ultrasound (Us) Examinationsmentioning
confidence: 99%
“…Therefore, other indicators to select patients who may have a higher risk of progression in HCC are necessary [10]. Retrospective studies indicate that the coarse nodular pattern is a risk factor for the development of HCC [11][12][13][14][15]. Coarse echo pattern is the most common one found in liver cirrhosis (LC) [11]; it is defined coarse nodular by the detection within the liver of small multiple hypoechoic nodular images (<1 cm) at US.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations